Gaseous emissions from wastewater facilities. (15th October 2020) - Koh, Sock‐Hoon; Shaw, Andrew R.
Abstract: A review of the literature published in 2019 on topics relating to gaseous emissions from wastewater facilities is presented. This review is divided into the following sections: odorant emissions from Water Resource Recovery Facilities (WRRFs); greenhouse gas (GHG) emissions; gaseous emissions from wastewater collection systems; physiochemical odor/emissions control methods; biological odor/emissions control methods; odor/GHG characterization and monitoring; and odor impacts/risk assessments. © 2020 Water Environment Federation Practitioner Points: Provide a quick reference list for readers who do not have time to go through the 2019 published articles. This prescreening of relevant literatures will save them time and effort. Utilities, engineers, and researchers can identify knowledge gaps, which help them to plan for future testing and R&D needs. Designers can make use of the lit review findings to support their design.